2018
DOI: 10.5588/ijtld.17.0363
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of treatment literacy materials for tuberculosis patients

Abstract: We found few examples of comprehensive, patient-centered documents. Work is needed to achieve consensus as to the essential elements of TB treatment literacy and to create additional materials for children, patients with drug-resistant TB, and those with lower literacy levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This is a point on which our department is currently working, as it could be an easy lever to activate. We try to implement a systematic written translation of TB related information for all patients in their own language, using a non-stigmatizing vocabulary and pictures, as described in the literature [34,35]. We are also currently working on picture-based flipcharts (thus overcoming language barrier and/or illiteracy), that illustrate the importance of remaining in prolonged isolation and taking anti-tuberculosis medications every day.…”
Section: Discussionmentioning
confidence: 99%
“…This is a point on which our department is currently working, as it could be an easy lever to activate. We try to implement a systematic written translation of TB related information for all patients in their own language, using a non-stigmatizing vocabulary and pictures, as described in the literature [34,35]. We are also currently working on picture-based flipcharts (thus overcoming language barrier and/or illiteracy), that illustrate the importance of remaining in prolonged isolation and taking anti-tuberculosis medications every day.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, though the patients were reluctant to engage actively, they still wanted to communicate with their HCPs to obtain necessary information. That information provided them with an opportunity to learn about and understand their condition30 and empowered them to contribute as active partners 31,32. Earlier studies have found that acquiring basic information from HCPs is a prerequisite for PE 33.…”
Section: Discussionmentioning
confidence: 99%
“…Topics which would have benefitted participants in this research included additional explanation about personal and family diagnoses, the TB latency cycle and TB transmission – key for dispelling stigma-informed myths about household infection prevention. This list is by no means comprehensive, and we agree with Brumwell et al (2018) that consensus is needed on a list of essential education and counselling topics in TB. However, such a list is insufficient without efforts to strengthen patient and family member participation in education and counselling.…”
Section: Discussionmentioning
confidence: 98%
“…Other researchers (e.g. Brumwell et al, 2018; McEwen, 2005; Moodley et al, 2020) have demonstrated that TB education and counselling can be imbalanced, containing a strong focus on biomedical instructions at the expense of more fulsome explanations which help patients and family members understand TB and manage the impacts on their everyday lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation